Analysis of the Integrated Water Resource Management in a Water Quality Management Area in the Philippines The Case of Meycauayan-Marilao-Obando River System - Malenab, Ma. Charisma (Journal of Environmental Science and Management, 2016)
This research evaluates the implementation and management of the Meycauayan- Marilao-Obando River System Water Quality Management Area (MMORS WQMA) in reference to the pillars of Integrated Water Resource Management (IWRM) using a multimethod approach. Research participants include representatives from regional regulatory agencies and local government units of seven cities and municipalities along the river system. Aside from ecosystem, institutional and socio-political drivers, the designation of MMORS as a WQMA was influenced by the shared common interest and endorsement of local stakeholders including financial support from international agencies. Also, an enabling policy environment that reflects IWRM pillars helped in the creation of MMORS WQMA. However, disparities in WQMA Governing Board (GB)’s and the local government units’ (LGUs) level of awareness and actual level of implementation of functions are observed, hence, the need for integration. The lack of a guiding system or framework in monitoring, evaluation and information management hinders better integration among the different agencies and LGUs in the MMO WQMA GB. Also, lack of financial, human and technical resources limit performance of the GB. Improving mechanisms may include approval of the National Water Quality Management Fund; development of financial and annual plans (with short-term targets), collaboration among GB members and capacity building.